Unlocking the Research Potential of Early Modern Dutch Maps - Leon van Wissen; Manjusha Kuruppath; Lodewijk Petram (European Journal of Geography)
Working from the GLOBALISE project, we have enhanced access to over 5,000 Dutch maps from the seventeenth and eighteenth centuries, renowned for their geographic and historical significance. We have laid the groundwork for enriching these maps with annotations and metadata following the International Image Interoperability Framework (IIIF) standards, directly linked to their digital representations from the collection-holding institutions. This approach ensures a FAIR framework for sharing research results and fosters collaborative annotation. We enriched the maps with georeferencing annotations and employed automated tools to extract toponyms and geographic features, enabling large-scale analysis. These annotations open new pathways for exploring understudied historical regions, such as early modern Kerala, and assessing Dutch colonial influence globally. By publishing our data early, we aim to encourage further collaborative refinements, allowing a wider scholarly community to improve and build upon this work. This approach highlights the potential of combining historical cartography with computational tools to empower large-scale geographic and historical research.